1992
DOI: 10.3354/meps081001
|View full text |Cite
|
Sign up to set email alerts
|

Significance of body size to the interaction between a larval fish {Mallolus villosus) and a vertebrate predator (Gasterosteus aculeatus)

Abstract: ABSTRACT. We investigated the influence of variations in the size of prey (Mallotus villosus) and a vertebrate predator (Gasterosteus aculeatus) on larval fish mortality rates during the period of yolk absorption using mid-size mesocosms (2.7 m". Increasing predator size increased mortality rates of capelin larvae. Variations in larval capelin size resulted in 2 distinct patterns. Between experimental trials, greater mean size of larval capelin in the mesocosm reduced mortality due to predation. Within an expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 49 publications
4
89
3
Order By: Relevance
“…This showed that the cumulative size-selective mortality was positively directed such that smaller individuals were more likely to survive. The higher probabilities of mortality among larger individuals have already been reported (Fuiman 1989, Litvak & Leggett 1992, Pepin et al 1992. There are various reasons for positive size-selective mortality.…”
Section: 'Bigger Is Better' and 'Growth-selective Predation' Hypothesesmentioning
confidence: 81%
“…This showed that the cumulative size-selective mortality was positively directed such that smaller individuals were more likely to survive. The higher probabilities of mortality among larger individuals have already been reported (Fuiman 1989, Litvak & Leggett 1992, Pepin et al 1992. There are various reasons for positive size-selective mortality.…”
Section: 'Bigger Is Better' and 'Growth-selective Predation' Hypothesesmentioning
confidence: 81%
“…Smaller larvae (in terms of biomass) hatched from smaller eggs (Giménez & Anger 2001), and these showed a lower survival and longer duration of development not only under ad libitum feeding conditions (present study) but also when they were exposed to periods of starvation (Giménez 2002). Under weak osmotic stress, high initial biomass at hatching was associated with high levels of reserves in advanced zoeal stages , most likely as a consequence of an enhanced ability of larger zoeae to capture and ingest prey (Pepin et al 1992).…”
Section: Effects Of Initial Egg Biomass and Larval Biomassmentioning
confidence: 87%
“…Although both invertebrate and vertebrate predators are known to include fish larvae in their diet, vertebrate predators such as planktivorous fishes have been shown to have the greatest impact on larval fish mortality (Fuiman & Gamble 1988, Litvak & Leggett 1992, Pepin et al 1992. As has been demonstrated for zooplankton, predation risk to fish larvae appears to be influenced by both body size (Litvak & Leggett 1992, Pepin et al 1992) and the presence of alternative prey (Bailey & Yen 1983, Pepin 1987). For example, several studies have found that the presence of alternative prey (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…Cod larvae were reared in ambient seawater from eggs collected from a laboratory broodstock. All larvae used in experiments were 5 to 7 d post-hatch and similar in size (mean length f 1 SE = 4.4 f 0.13 mm), to eliminate effects due to larval age and size on risk to predation (Litvak & Leggett 1992, Pepin et al 1992.…”
Section: Methodsmentioning
confidence: 99%